Sea scorpions [book with audioplayer] - Moening, Kate (Moening, Kate. Ancient marine life., 2023)
Sea scorpions were the biggest arthropods to ever exist. The biggest grew over 8 feet long! In this hi/lo title, readers will discover the lives of sea scorpions as they swam through prehistoric oceans. Leveled text and colorful illustrations show off sea scorpions' body parts, favorite foods, behaviors, and extinction. Special features map the prehistoric world, show off the animals' size, call out favorite foods, and highlight an important fossil discovery. The book closes with a full-spread profile that puts important information about sea scorpions in one place!